PENGARUH PRODUKSI PERTANIAN, LUAS LAHAN, DAN PENDIDIKAN TERHADAP PENDAPATAN PETANI DAN ALIH FUNGSI LAHAN PERTANIAN DI PROVINSI BALI - Aryawati, Ni Putu Riska; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 9, September 2018 (pp. 1826-2070), 2018)
Indonesia is an agrarian country where agriculture is the main base of the national economy. Agricultural sector is a very important sector role in the economy.The purpose of this research is to find out the direct and indirect effect of agricultural production, land area and education to farmer income and agriculture land conversion in Province of Bali. This research is quantitative research which is analyzed by associative by explaining the relation between one variable to another variable. Analytical technique of this study is path analysis (path analysis). The conclusions of this research are as follows: 1). Agricultural Production, Land Area and Education have a positive and significant impact on farmers' income in Bali Province. 2). Agricultural Production, Land Area of ??Education and Income of Farmers have positive and significant impact to the Transfer of Agricultural Land Function in Bali Province. 3). Agricultural Production, Land Area and Education significantly influence the conversion of agricultural land through the income of farmers in Bali Province, so the income of farmers is right to mediate agricultural production, land area and education on the conversion of agricultural land.